The Recovery Strategy of Mangrove Tourism after Covid-19 Pandemic in Bintan Island, Indonesia - Khairunnisa Khairunnisa (EDP Sciences, 2021)
The Corona Virus Disease 2019 (Covid-19) has been confirmed as pandemic by the World Health Organization (WHO). Every country in the world is affected by this disease, including Indonesia. Covid-19 impacts not only public health but also other sectors such as tourism. This study aims to discover the solution to recover mangrove tourism after the pandemic. This study formulates the mangrove tourism recovery strategy after Covid-19 that conducted from April to August 2021 in Bintan Islands, Indonesia. The recovery strategy using Strength, Weakness, Opportunity, and Threat (SWOT) and Analytical Hierarchy Process (AHP) analysis. The result shows that the strength of mangrove tourism in Bintan Island is the magnificence of the mangrove itself, the community-based tourism, various and unique tourism activities, etc. The weakness is incomplete facilities, lack of promotion, etc. The recovery strategy priority is mangrove tourism management that performed by BUMDes, Establishment of Pengudang Village Tourism and Cultural Heritage, Training and Mentoring of Mangrove Tourism Managers.